Neutrophil-Derived Interleukin 16 in Premetastatic Lungs Promotes Breast Tumor Cell Seeding. (26th October 2017) - Donati, Kim; Sépult, Christelle; Rocks, Natacha; Blacher, Silvia; Gérard, Catherine; Noel, Agnès; Cataldo, Didier
The premetastatic niche in distant organs prior to metastatic cell arrival emerged as an important step in the metastatic cascade. However, molecular mechanisms underlying this process are still poorly understood. In particular, whether neutrophil recruitment at a premetastatic stage promotes or inhibits metastatic cell seeding has to be clarified. We aimed at unraveling how neutrophil infiltration in lung parenchyma induced by the distant primary tumor influences the establishment of lung metastasis. Elevated neutrophil counts and IL-16 levels were found in premetastatic lungs in a syngenic mouse model using 4T1 tumor cells. 4T1 cell–derived soluble factors stimulated IL-16 secretion by neutrophils. The functional contribution of IL-16 is supported by metastasis burden reduction in lungs observed on instillation of an IL-16 neutralizing antibody. Moreover, IL-16 promotes in vitro 4T1 cell adhesiveness, invasiveness, and migration. In conclusion, at a premetastatic stage, neutrophil-derived IL-16 favors tumor cell engraftment in lung parenchyma.